Public perception of the physician associate profession in the UK: a systematic review - Rhys Swainston; Yingxi Zhao; Eli Harriss; Attakrit Leckcivilize; Mike English; Shobhana Nagraj (BMC, 2024)
Abstract Background The physician associate (PA) role within the NHS is currently under scrutiny due to recent legislative changes and concerns about their scope of practice within primary and secondary healthcare. There is currently limited knowledge of public understanding of PAs and their levels of satisfaction with PAs. This review synthesises the evidence relating to patients' and potential patients' understanding of and satisfaction with the PA profession in the UK. Methods We systematically searched Ovid MEDLINE, Ovid EMBASE, Ovid PsycINFO, EBSCOhost CINAHL, Education Resources Information Centre (ERIC), ProQuest Dissertations and Theses Global, and Scopus databases for empirical studies of patient understanding of PAs or satisfaction with PAs. We included quantitative, qualitative, and mixed-methods studies looking at PAs in primary and/or secondary care. Quality appraisal was conducted using the CASP Critical Appraisal checklists. A reflexive thematic analysis was used to synthesise data and the GRADE-CERqual method was used to assess the certainty of the themes. Results A total of 18 papers involving 15 studies were included in the review. Findings revealed that patients had limited understanding of the PA role with many mistaking PAs for doctors and other healthcare professionals. Patients were confused by the lack of PA prescribing rights. There was receptivity to learn more about the PA role. The evidence suggests that patients had a largely positive view of PAs after an encounter, despite their lack of knowledge about the role. Many patients expressed a willingness to be seen by PAs in future and viewed them as a useful part of the wider healthcare system. Conclusion In the UK, there is limited information about, and understanding of, the PA role. Nevertheless, patients were largely satisfied with the quality of care they receive from PAs during consultations. Our findings suggest a need for comprehensive public information regarding the roles and scope of practice of PA's, and to provide the public and patients with clear expectations of their relative strengths and limitations. Further research might determine if these findings are specific to PAs, or reflect wider issues affecting public perception of other cadres of healthcare professionals.